2020
DOI: 10.1186/s12884-020-03431-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-breastfeeding stress response and breastfeeding self-efficacy as modifiable predictors of exclusive breastfeeding at 3 months postpartum: a prospective cohort study

Abstract: Background The rate of exclusive breastfeeding at 3 months postpartum is only 50% in Japan. In order to increase this rate, we aimed to examine modifiable factors related to exclusive breastfeeding at 3 months postpartum by focusing on breastfeeding-related and psychosocial variables at 1 month postpartum. Methods This prospective cohort study was conducted at a secondary medical care center in Osaka, Japan from February 2017 to October 2018. Demog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
2
16
0
3
Order By: Relevance
“…In the present study, exclusive breastfeeding within 42 days after childbirth was associated with a reduced risk of postpartum PTSD, which may be mediated through the regulation of stress biomarkers such as cortisol [ 27 29 ]. One study has shown that women with PTSD had very high levels of cortisol in the postpartum period [ 30 ], raising the possibility that postpartum PTSD might be linked to the dysregulation of cortisol. Another study has found that lower cortisol levels after breastfeeding were associated with exclusive breastfeeding practices [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, exclusive breastfeeding within 42 days after childbirth was associated with a reduced risk of postpartum PTSD, which may be mediated through the regulation of stress biomarkers such as cortisol [ 27 29 ]. One study has shown that women with PTSD had very high levels of cortisol in the postpartum period [ 30 ], raising the possibility that postpartum PTSD might be linked to the dysregulation of cortisol. Another study has found that lower cortisol levels after breastfeeding were associated with exclusive breastfeeding practices [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological discomfort can also trigger the mother to discontinue breastfeeding ( 32 33 ). According to the findings of this study, breastfeeding mothers face challenges such as nipple pain, nausea, vomiting and dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…The pain felt when the baby sucks the milk causes stress in the mother. This condition is due to increased cortisol, which plays an essential role in stress ( 33 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mothers often have to resort to artificial milk, without fulfilling their wishes to breastfeed. Mothers who breastfeed are more likely to continue breastfeeding despite being provided with breast support (Shiraishi et al, 2020). This support is provided mainly by midwives in Japan; their breast care method involves the use of hands only.…”
Section: Introductionmentioning
confidence: 99%